SELECTION OF SUITABLE SAMPLING TOOL FOR RELIABLE SOIL SAMPLING NOT ONLY AFTER RADIOLOGICAL ACCIDENT - Setnička, Michal; Kroupa, Tomáš; Čtvrtečková, Alena; Marek, René (Radiation protection dosimetry, 2019)
The objective of this research was to develop a sampling protocol for contaminated soils after a large radiological accident. One of the criteria for good sampling method is reproducibility and accuracy of large number of samples collected in short time. Members of the chemical laboratories of the Fire Rescue Service of the Czech Republic (FRS CR), which are included in Radiation Monitoring Network, tested four tools in different soil types. More than 100 samples were collected. Root auger and square soil sampler seem to be the best for reliable soil sampling. Modifications of the root auger decreased of relative error of sampling to 7.5%. The root auger is recommended as a first-choice sampling tool based on: (1) ease, (2) operator safety, (3) collection of a representative sample (4) applicability to most soil types and (5) enabling collection of depth-discrete samples.
Keywords: Soil Pollutants, Radioactive; monitorování radiace; řízení kvality; Quality Control; Radioactive Fallout; odběr biologického vzorku; radioaktivní spad; Humans; Specimen Handling; radioaktivní látky znečišťující půdu; lidé; Radiation Monitoring